Evaluation of Chemical Compounds and their Relationship to the Breaking Point after adding Chlorine to Water - Estabraq Ali Hameed (Tikrit Journal of Pure Science)
Evaluation of the chemical compounds formed during the process of sterilizing water with chlorine is a very important point. During sterilization the water goes through three stages each stage resulting different chemical compounds. In the first stage, chlorine reacts with iron, magnesium and nitrates. In the second stage it reacts with ammonia and in the third stage it reacts with the organic compounds in the water. Chlorine in these three stages is called combined chlorine. Then it reaches the breaking point, after this point the water must be free from side chemical compounds, and chlorine after this point is called the residual free Chlorine. Drinking water samples were taken from 3 city in Kirkuk governorate, and the concentrations of magnesium, nitrate, sulfate, acetic acid derivatives, as well as the halomethane group in addition to some physical determinants were evaluated.